10(w-2)-3(4w+6)-5w=2(-w+3)-6(2w+1)-4

Simple and best practice solution for 10(w-2)-3(4w+6)-5w=2(-w+3)-6(2w+1)-4 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 10(w-2)-3(4w+6)-5w=2(-w+3)-6(2w+1)-4 equation:


Simplifying
10(w + -2) + -3(4w + 6) + -5w = 2(-1w + 3) + -6(2w + 1) + -4

Reorder the terms:
10(-2 + w) + -3(4w + 6) + -5w = 2(-1w + 3) + -6(2w + 1) + -4
(-2 * 10 + w * 10) + -3(4w + 6) + -5w = 2(-1w + 3) + -6(2w + 1) + -4
(-20 + 10w) + -3(4w + 6) + -5w = 2(-1w + 3) + -6(2w + 1) + -4

Reorder the terms:
-20 + 10w + -3(6 + 4w) + -5w = 2(-1w + 3) + -6(2w + 1) + -4
-20 + 10w + (6 * -3 + 4w * -3) + -5w = 2(-1w + 3) + -6(2w + 1) + -4
-20 + 10w + (-18 + -12w) + -5w = 2(-1w + 3) + -6(2w + 1) + -4

Reorder the terms:
-20 + -18 + 10w + -12w + -5w = 2(-1w + 3) + -6(2w + 1) + -4

Combine like terms: -20 + -18 = -38
-38 + 10w + -12w + -5w = 2(-1w + 3) + -6(2w + 1) + -4

Combine like terms: 10w + -12w = -2w
-38 + -2w + -5w = 2(-1w + 3) + -6(2w + 1) + -4

Combine like terms: -2w + -5w = -7w
-38 + -7w = 2(-1w + 3) + -6(2w + 1) + -4

Reorder the terms:
-38 + -7w = 2(3 + -1w) + -6(2w + 1) + -4
-38 + -7w = (3 * 2 + -1w * 2) + -6(2w + 1) + -4
-38 + -7w = (6 + -2w) + -6(2w + 1) + -4

Reorder the terms:
-38 + -7w = 6 + -2w + -6(1 + 2w) + -4
-38 + -7w = 6 + -2w + (1 * -6 + 2w * -6) + -4
-38 + -7w = 6 + -2w + (-6 + -12w) + -4

Reorder the terms:
-38 + -7w = 6 + -6 + -4 + -2w + -12w

Combine like terms: 6 + -6 = 0
-38 + -7w = 0 + -4 + -2w + -12w
-38 + -7w = -4 + -2w + -12w

Combine like terms: -2w + -12w = -14w
-38 + -7w = -4 + -14w

Solving
-38 + -7w = -4 + -14w

Solving for variable 'w'.

Move all terms containing w to the left, all other terms to the right.

Add '14w' to each side of the equation.
-38 + -7w + 14w = -4 + -14w + 14w

Combine like terms: -7w + 14w = 7w
-38 + 7w = -4 + -14w + 14w

Combine like terms: -14w + 14w = 0
-38 + 7w = -4 + 0
-38 + 7w = -4

Add '38' to each side of the equation.
-38 + 38 + 7w = -4 + 38

Combine like terms: -38 + 38 = 0
0 + 7w = -4 + 38
7w = -4 + 38

Combine like terms: -4 + 38 = 34
7w = 34

Divide each side by '7'.
w = 4.857142857

Simplifying
w = 4.857142857

See similar equations:

| 90-12y=-90 | | -2x+4=20 | | 6*7*h=378 | | 6x+x=245 | | 8w+5=13 | | 67h=378 | | 10x(-7)= | | -7x+6(-1)=-42 | | 7/8x-7/8=5 | | 334=5x+274 | | 10=5x+274 | | 67=5x+274 | | 122=5x+274 | | 12=5x+274 | | 4x+1=2x+21 | | y=5x+274 | | 70+30x=230+14x | | 80+50x=240+26x | | 8m+1=3 | | 0.13+0.03(60000-x)=6000 | | 80+30x=240+14x | | x-5=10/5 | | 80+30x=240+7x | | 80+9x=240+30x | | Z+18=2 | | 2/4+x=5 | | 2/5+x=4 | | 2/5+x=3 | | -(7m+2)-6(3m-1)=2m-2(4m+5) | | 4/5+x=2 | | 0.15+0.05(50000-x)=5000 | | c^2-7c+10=0 |

Equations solver categories